On the design of OTA-C based field programmable analog arrays for continuous time low frequency applications. (September 2020) - Diab, Maha S.; Mahmoud, Soliman A.
Abstract: This work focuses on proposing FPAA architecture based on operational transconductance amplifier (OTA) as the basic block for low frequency continuous time signal processing. Two FPAA architectures are presented after a step by step development of the design structure. The architectures eliminate the use of switches for signal routing, instead they allow reconfigurability using a selecting network composed of OTAs. The proposed architectures demonstrate flexibility in architecture allowing the expansion of the basic structure. Both architectures allow the implementation of individual independent circuits with an option of cascading if required. Multiple filter circuits can be mapped on the FPAA with independent control and reconfigurability of gain, bandwidth, and notch frequency, thus allowing the use of the FPAA as a filter bank. As for the provided cascading feature, it allows the implementation of a system or a set of cascaded filters as desired by designer. Validation of proposed FPAA architecture and its characteristics is examined through simulation on LTspice using 90 nm CMOS technology with supply voltage of ±0.6 V . A single 4th-order lowpass filter is implemented first and then a combination of amplifier, notch filter and lowpass filter is implemented. Simulation results of the filters on proposed FPAA is compared to results acquired from simulation of the circuits alone (off-FPAA) showing excellent agreement between both results, hence confirming the proposed FPAA architecture.